Technology adoption in markets with network effects: Theory and experimental evidence - Claudia Keser; Irina Suleymanova; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
We examine a technology adoption game with network effects in which coordination on technology A and technology B constitute a Nash equilibrium. Coordination on technology B is assumed to be payoff-dominant. We define a technology's critical mass as the minimum share of users necessary to make the choice of this technology a best response for any remaining user. We show that the technology with a lower critical mass is risk-dominant and is chosen by the maximin criterion. We present experimental evidence that both pay-off dominance and risk dominance explain participants' choices. The relative riskiness of a technology can be proxied using technologies' critical masses or stand-alone values.
Keywords: C72; C91; D81; 330; Network Effects; Critical Mass; Coordination; Riskiness